Predicting social entrepreneurial intention: a meta-analytic path analysis based on the theory of planned behavior - Zaremohzzabieh, Zeinab; Ahrari, Seyedali; Steven, Eric Krauss; Abu Samah, Asnarulkhadi; Lee, Kwan Meng; Ariffin, Zaifunizam (Elsevier, 2019)
The aim of this meta-analysis was to examine the applicability of the theory of planned behavior for predicting social entrepreneurial intention (SEI). A random-effects meta-analysis of zero-order correlations reported in the findings of 31 studies (37 samples, n = 14,318) was performed, and correlations between the constructs in the TPB model and SEI were scrutinized through the application of meta-analytic structural equation modeling (MASEM) based on a pooled correlation matrix. Two alternative models were proposed and then evaluated, suggesting alternative formulations of the antecedents of SEI by modifying the relationships between key TPB constructs and intentions. The findings showed better fit of the alternative models than the original TPB model at predicting SEI. The findings also revealed that the strength of the two models enriches the TPB through the additional factors. We recommend that scholars adopt this technique when synthesizing evidence across assessments of TPB.